Effect of mechano-chemical pretreatment on valorizing plant waste for 5-hydroxymethylfurfural under microwave hydrothermal treatment. (December 2021) - Zhou, Ying; Shao, Yuchao; Zhou, Dan; Meng, Yanjun; Shen, Dongsheng; Long, Yuyang
Abstract: Plant waste (PW) is a common and abundant renewable biomass resource whose total amount is constantly increasing and accounts for up to 50% of municipal solid waste. This study aims to develop a valorization method for PW. A two-stage treatment method combining mechanical ball milling (BM) and microwave hydrothermal treatment (MHT) was investigated. BM can effectively destroy the crystallization of cellulose and reduce the particle size to increase the specific surface area and improve the MHT efficiency. The BM-MHT process could improve the 5-hydroxymethylfurfural (HMF), which is significantly higher than physical methods like grinding, ultrasonic and liquid nitrogen treatment. The BM conditions were further optimized by using a Box-Behnken Design with response surface methodology. The model showed that the highest HMF yield could reach 1.8% at 150 °C in MHT process after BM. An economic analysis indicated that BM-MHT offers a green treatment method with great economic benefits. It provides a novel valorization strategy for organic waste like PW. Graphical abstract: Image 1 Highlights: Ball milling can effectively depolymerize plant waste. Ball milling combined with microwave hydrothermal treatment can valorize plant waste. The highest yield of 5-hydroxymethylfurfural from plant waste was 1.81%.